Novel Nanomaterials - Krishnamoorthy, Karthikeyan (IntechOpen, 2021)
This book discusses novel nanomaterials and their various aspects. Chapters provide detailed information on new preparation routes for novel nanomaterials and their applications in supercapacitors, nanogenerators, removal of industrial pollutants, biosensors, self-cleaning coatings, aquatic robotics, and the construction industry.